The implementation of Scientific Approach in English teaching through Inquiry-based Learning at the first year of SMP N 1 Purwodadi in 2014/2015 academic year - Kurniawati Sagita, Yeyen; , Mauly Halwat Hikmat, Ph. D; , Nur Hidayat, S.Pd (2015)
This research paper is aimed at describing the implementation of Scientific Approach in English Teaching through Inquiry-based Learning at the first year of SMP N 1 Purwodadi in 2014/2015 academic year. This study describes to the implementation of Scientific Approach in English Teaching through Inquiry Based Learning and the problems faced by the teacher in applying this approach at the first year of SMP N 1 Purwodadi in 2014/2015 academic year. The type of this research is general qualitative, using descriptive qulitative method the data obtained are from event, informant and document. The techniques of collecting data were observation, interview and document analysis of teaching and learning activities in English teaching to clarify the implementation of Scientific Approach through Inquiry-based Learning and problem faced by the teacher. The result of this study shows the of procedures of Inquiry-based Learning are of: 1) observing, 2)asking, 3)experimenting, 4) associating and 5) communicating. The problems faced by the teacher are: 1) the limitation of time, 2) lack of teaching media, 3) low ability and activeness of the students.